Establishing a causal link between the human papilloma virus and oral fibromas - Gargi Sarode; Urmi Ghone; Renuka Gophane; Nidhi Kumari; Sachin C. Sarode (Oral Oncology Reports)
Fibroma, a benign tumour of fibrous connective tissue, can be seen as a reactive connective tissue hyperplasia in response to trauma and irritation. They typically have a firm consistency, are nodular and asymptomatic, have a colour that is similar to the mucosa, a sessile base, a smooth surface, and are situated in the buccal mucosa along the line of occlusion, tongue, and lip mucosa. We retrospectively investigated total 79 cases and intriguingly, 41 cases were not associated with any history or clinical evidence of chronic trauma of dental origin suggesting different pathogenesis mechanism. Out of 79 cases of oral fibroma, 18 showed evidence of koilocytes in the overlying epithelium with 14 cases not associated with history of any trauma. This might suggest the cause and effect relationship between HPV and oral fibromas, however, the possibility of secondary infection in already existing fibroma can be considered. This intriguing finding prompt us to propose a novel hypothesis explaining the role of human papilloma virus in the pathogenesis of fibroma.